Effect of dietary biscuit waste on performance and carcass characteristics of broilers (2013)
A study was conducted for 8 weeks to investigate the effect of dietary biscuit waste (BW) replacing maize (M) on performance and carcass characteristic of broilers. A total of 175 day old marshal broiler chicks were used for this study. They were completely randomized and divided into five treatments. Each treatment had five replicates of seven birds per replicate. Five experimental diets were formulated as follows; A: (100%M: 0%BW), B: (75% M: 25%BW), C: (50%M: 50%BW), D: (25%M: 75%BW), E: (0%M: 100%BW) at both starter and finisher phases. Performance indices measured were feed intake, weight gain and feed conversion ratio. The feed intake (F.I.) was affected with increasing level of biscuit waste. There were significant differences (p<0.05) across the treatments with treatment A having the highest value of 2.92kg for F.I and treatment E having the least value of 2.51kg while treatments B, C and D followed the same trend having the following values of 2.73kg, 2.70kg and 2.61kg respectively. Average weight gain showed that there were no significant differences (p>0.05) across the treatments, the values obtained were 1.13kg, 1.09kg, 1.10kg, 1.12kg and 1.10kg for treatments A, B, C, D and E respectively. Feed conversion ratio showed significant differences (p˂0.05) as birds in treatments C, D and E recorded lower values of 2.47%, 2.37% and 2.33% respectively while birds on treatment A had highest value of 2.60%. The carcass weights expressed as percentages of live weights (LW) did not show any significant differences (p>0.05). The result for breast weights showed significant differences (p˂0.05) as birds on treatments four (25% M: 75% (BW) and five (0%M: 100% BW) had lower values of 10.05% (LW) and 11.20% (LW) respectively. Surprisingly, birds on treatment two (75% M 25% BW) had the highest breast meat value of 16.75%. The percentage organ weights showed no significant differences (p>0.05) between liver, heart and spleen but the gizzard weights were significantly different among the treatments with the control having the highest value of 2.88% (LW). It was concluded that biscuit waste could be used as feed for broilers up to 50% replacement levels for maize at the starter and finisher phases without compromising performance and carcass value of broilers.